2013
DOI: 10.4236/health.2013.512288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the average access to care and continuity of care patients in Tehran teaching hospitals

Abstract: Background: Standards of Joint Commission International emphasize on the organizational performance level in basic functional domains including patient right, patient care, medical safety and infection control. These standards are focused on two principles: expectations of the actual organizational performance and assessment of organizational capabilities to provide high quality and safe health care services. The aim of this study is to evaluate the possibility of improvement in Access to Care and Continuity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Occupational capabilities and graduates efficiency in medical sciences fields depend on the level of achieving objectives in educational programs in order to present remedial, hygienic services, research and educational programs, for promotion of individual and society health level and if educational programs haven't developed and performed correctly, it can cause irreparable damages and economic, cultural and social serious effects on individual and graduates as well as university management and the validity (Farzianpour et al, 2013c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational capabilities and graduates efficiency in medical sciences fields depend on the level of achieving objectives in educational programs in order to present remedial, hygienic services, research and educational programs, for promotion of individual and society health level and if educational programs haven't developed and performed correctly, it can cause irreparable damages and economic, cultural and social serious effects on individual and graduates as well as university management and the validity (Farzianpour et al, 2013c).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in educational evaluation showed average of the function of educational evaluation in basic sciences groups and clinical groups were respectively 76.4 and 86.6% while grand average of the function of clinical groups and basic sciences groups was 80.5% (Farzianpour et al, 2013b;2013c). Rabbani et al (2006) showed general average of the function of internal evaluation in Department of pediatrics faculty of medicine were respectively %53.3 in 2003 and %75.3 in 2004. In university educational system, it is possible to use educational evaluation in electing students, scientific board and curriculum and in general the other educational system inputs in addition, it supervises on system process performing and finally using evaluation directs outputs and system consequences optimally (Farzianpour et al, 2011d).…”
Section: Discussionmentioning
confidence: 96%
“…The average hospitalization period for men and women patients at the wards were about 23 and 22 days, respectively, which does not show any statistical differences at the error level of five percent (P > 0.05). However, in the study conducted by Farzianpour et al it was found that there were significant relationships between the variables of gender, age, marital status, place of residence, occupation, referral types, type of insurance, reasons for hospitalization, and the conditions of the patients discharged from hospitals with their hospitalization periods [1] [2].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital infections are infections caused from 48 to 72 hours after hospitalization or, at the maximum, six weeks after discharge from hospitals. These infections are not latent in patients but rather develop in them for the first time [1] [2]. Hospital infections prolong patient hospitalization, raise patient mortality rate, and, as a result, increase hospital expenses [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation